2020
DOI: 10.3389/fgene.2020.587509
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune Response to Sacbrood Virus Infection in Apis cerana Under Natural Condition

Abstract: Chinese sacbrood virus (CSBV) is a serious threat to eastern honeybees (Apis cerana), especially larvae. However, the pathological mechanism of this deadly disease remains unclear. Here, we employed mRNA and small RNA (sRNA) transcriptome approach to investigate the microRNAs (miRNAs) and small interfering RNAs (siRNAs) expression changes of A. cerana larvae infected with CSBV under natural condition. We found that serine proteases involved in immune response were down-regulated, while the expression of siRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Bees belonging to Apis mellifera are more resistant to SBV infection compared to Apis cerana bees [13,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bees belonging to Apis mellifera are more resistant to SBV infection compared to Apis cerana bees [13,38].…”
Section: Discussionmentioning
confidence: 99%
“…At a time when the honey bee's body is developing new defenses against the pathogen, the latter is forced to adapt its own strategy of invasion and infection to counteract the host's immune defenses. Therefore, it has been suggested that the more stable the immunity of bees, the more often more pathogenic strains will be detected, and this in turn will accelerate the evolution of pathogens [27,[37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, by performing small RNA-seq (sRNA-seq) and bioinformatics, we discovered 560 miRNAs in the Apis mellifera ligustica larval guts [ 23 ] and deciphered the expression profile as well as regulatory network of miRNAs across the developmental process of larval guts [ 24 ]. Currently, limited studies have shown that A. cerana miRNAs are potentially involved in response to fungi or viruses [ 25 , 26 ]. For example, Deng et al [ 26 ] identified a total of 23 differently expressed miRNAs (DEmiRNAs) in A. cerana larvae upon CSBV infection and inferred that ame-miR-3759 may play a key part in melanin synthesis during larval response.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, limited studies have shown that A. cerana miRNAs are potentially involved in response to fungi or viruses [ 25 , 26 ]. For example, Deng et al [ 26 ] identified a total of 23 differently expressed miRNAs (DEmiRNAs) in A. cerana larvae upon CSBV infection and inferred that ame-miR-3759 may play a key part in melanin synthesis during larval response. Recently, we identified 435 miRNAs in the larval guts of A. c. cerana , the nominate subspecies of A. cerana , based on sRNA-seq and bioinformatics and further confirmed the sequences of six miRNAs and the expression of five miRNAs using molecular approaches [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA) is a class of small (18–24 nt), single-strand, and endogenous ncRNA that plays important roles in the post-transcriptional regulation of target gene expression [ 16 , 17 ] related to various biological processes, such as tissue development [ 18 ]. Previous studies on honeybee miRNAs revealed their key roles in mediating diverse physiological processes, such as caste differentiation [ 19 , 20 ], division of labor [ 21 , 22 ], memory formation [ 23 , 24 ], queen reproductive performance [ 25 , 26 ], immune defense [ 27 , 28 ], and embryonic and midgut development [ 29 , 30 ]. However, little is known about whether/how miRNAs regulate the HPGs development in worker bees.…”
Section: Introductionmentioning
confidence: 99%